Influence of Different Bacteria Inocula and Temperature Levels on the Chemical Composition and Antioxidant Activity of Prickly Pear Vinegar Produced by Surface Culture - Ikram Es-sbata; Remedios Castro; Yolanda Carmona-Jiménez; Rachid Zouhair; Enrique Durán-Guerrero (Foods, 2022)
This work intends to determine the effect on the aroma profile, phenolic content and antioxidant activity of prickly pear vinegars produced by the surface culture at two different fermentation temperatures and using different acetic acid bacteria (AAB) inocula. Prickly pear wine was fermented at two temperature levels (30 and 37 °C) by using bacteria inocula containing Acetobacter, Gluconobacter or a mixture of bacteria isolated from Sherry vinegars. Eighty-five individual volatile compounds from different families and sixteen polyphenolic compounds have been identified. It was confirmed that the highest temperature tested (37 °C) resulted in a lower concentration of volatile compounds, while no significant effect on the vinegars’ volatile composition could be associated with the AAB inoculum used. Contrariwise, the highest content of polyphenolic compounds was detected in those vinegars produced at 37 °C and their concentration was also affected by the type of AAB inoculum used. Prickly pear wine displayed greater antioxidant activity than juices or vinegars, while the vinegars obtained through the mixture of AAB from Sherry vinegar showed higher antiradical activity than those obtained through either of the two AAB genera used in this study. It can be therefore concluded that, although the volatile content of vinegars decreased when fermented at a higher temperature, vinegars with a higher content in polyphenols could be obtained by means of partial fermentations at 37 °C, as long as thermotolerant bacteria were employed.